Pengaruh Earning Per Share Net Profit Margin dan Tobin’s Q Terhadap Return Saham Syariah Sektor Kesehatan di Bursa Efek Indonesia - Lestari, Lestari; Erdiana, Atty (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to determine the effect of Earning per share (EPS), Net Profit Margin (NPM) and Tobin's Q on Islamic stock returns in the health sector on the Indonesia Stock Exchange (IDX). The object of this research is the health sector's sharia stocks, totaling 22 shares. The sampling method used is purposive sampling with the criterion that the issuer has complete financial reports from 2019-2022, and found 14 stocks that meet the criteria. This study uses multiple linear regression analysis techniques which are used to examine the effect of EPS, NPM and Tobin's Q on sharia stock returns in the health sector. The results of the research show that EPS, NPM and Tobin's Q do not have a significant effect on the return of sharia stocks in the health sector on the Indonesia Stock Exchange (IDX).